The University And Its Role in the Process of European Integrations: The Dystopian Fairy Tale of Serbian University (Politeja, 2019)
The University And Its Role in the Process of European Integrations. The Dystopian Fairy Tale of Serbian UniversityThe paper discusses the contemporary social role of the university in the three referent contexts: (a) the wider global context, (b) the regional context of European integrations, and (c) the local context of Serbian Society. The analysis discusses challenges of global context and university transformation, initial ideas of the Bologna process and the main directions of its implementation, and contemporary political and social challenges with the relationship between the university and its referent social environment and the value concepts shaping that relation. The latest tendencies of the abandonment of the university from its civil mission (Ćulum and Ledić, 2011) as one of the fundamental value concepts of modern universities has led to new escapist strategy that breaks the links between the university and the social environment in an almost artificial way. The paper discuss this tendency on the example of Serbian society and its university system, showing that the Serbian project of European integration has reached the point where it is necessary to articulate future directions of development so that they do not spontaneously take on malignant forms. On the one hand, breaking the link between the university and community jeopardizes the survivalof the university as we know it, and on the other hand, it eliminates serioussocial dialogue on the directions of future development.